Design for Stability in Transport Logistics - Definition, Concepts and Evaluation - Kunert, Christoph (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2018)
Lean management describes a set of methods combined with a management philosophy which aims at eliminating waste in logistics processes. In production logistics, lean is already widespread and applied successfully. Research has shown that lean also works in a warehousing environment. In transport logistics, lean is still at a low level of maturity in both research and practice. This work contributes to closing this gap by introducing Heijunka leveling to transport logistics.